The jurisdictional delimitation in the Chinese Anti-Monopoly Law public enforcement regime: the inevitable overstepping of authority and the implications. (25th October 2017) - Yan, Xingyu
Abstract: Following the adoption of the Anti-Monopoly Law (AML) in 2007, China established a public enforcement regime that has three equal-ranking authorities. The legislative history of the AML suggests that this was a backward-looking compromise reached between the three central administrative agencies (the Ministry of Commerce (MOFCOM), the National Development and Reform Commission (NDRC), and the State Administration for Industry and Commerce (SAIC)), instead of a forward-looking design choice. This article focuses on the jurisdictional delimitation between the NDRC and the SAIC, a delimitation assigning the enforcement responsibilities based on whether an allegedly anticompetitive conduct is price related or not. This article first describes the jurisdictional delimitation as defined in the relevant legal documents. On that basis, it examines the legal and the economic rationales behind this delimitation. Subsequently, this article investigates to what extent this delimitation has been adhered to in practice, and there it identifies three problematic scenarios, which indicate the inevitability of the two agencies overstepping their respective authority in practice. This article finds that this delimitation is likely to induce the following problems: uncertainty on supplementary enforcement and follow-on civil actions, uncontrolled agency discretion, and distortive theories of harm. Therefore, it suggests that this jurisdictional delimitation should be removed.